Respuesta :

By applying the functional theory related to binary operations of functions, we conclude that the resulting expression is equal to [tex](f \,\circ \,g) (x) = \frac{\sqrt[3]{3\cdot x} }{3\cdot x + 2}[/tex].

How to find the expression of a division between two functions

In functional theory, there are five operations that can be used between two functions:

  1. Addition - (f + g) (x) = f(x) + g(x)
  2. Subtraction - (f - g) (x) = f(x) - g(x)
  3. Multiplication - (f · g) (x) = f(x) · g(x)
  4. Division - (f/g) (x) = f(x) / g(x)
  5. Composition - (f ο g) (x) = f (g (x))

In this question we are asked to derive the expression of the division between two functions given. If we know that [tex]f(x) = \sqrt[3]{3\cdot x}[/tex] and g(x) = 3 · x + 2:

[tex](f \,\circ \,g) (x) = \frac{\sqrt[3]{3\cdot x} }{3\cdot x + 2}[/tex]

By applying the functional theory related to binary operations of functions, we conclude that the resulting expression is equal to [tex](f \,\circ \,g) (x) = \frac{\sqrt[3]{3\cdot x} }{3\cdot x + 2}[/tex].

Remark

The statement is poorly formatted and reports many typing mistakes. Correct statement is shown below:

Let [tex]f(x) = \sqrt[3]{3\cdot x}[/tex] and g(x) = 3 · x + 2. Find (f/g) (x).

To learn more on functions: https://brainly.com/question/12431044

#SPJ1